Generation of an ultrabroadband supercontinuum in the mid-infrared region using dispersion-engineered GeAsSe photonic crystal fiber - Ahmad, Harith; Karim, Mohammad Rezaul; Ghosh, Souvik; Rahman, B.M. Azizur (Springer, 2018)
An ultrabroadband mid-infrared (MIR) region supercontinuum (SC) is demonstrated numerically through dispersion-engineered traditional chalcogenide (ChG) photonic crystal fiber (PCF). By varying structural parameters pitch (hole to hole spacing) and air-hole diameter to pitch ratio, a number of 10-mm-long hexagonal PCFs made employing GeAsSe ChG glass as a core and air-holes of hexagonal lattice running through their lengths as a cladding are optimized to predict an efficient mid-infrared region SC spectral emission by pumping them using a tunable pump source between 2.9 and 3.3 µm. Simulations are carried out using an ultrashort pump pulse of 100-fs duration with a low pulse peak powers of between 3 and 4 kW into the optimized designs. It is found through numerical analysis that efficient SC spectral broadening with flattened output can be obtained by increasing the PCF pitch rather than increasing the PCF cladding containing air-hole diameter although a larger nonlinear coefficient could be obtained through increasing air-hole diameter of an optimized design. Simulation results show that the SC spectra can be broadened up to 12.2 µm for a certain design with a peak power of 3 kW. Using a peak power of 4 kW, it is possible to obtain SC spectral broadening beyond 14 µm with an optimized design spanning the wavelength range from 1.8 to 14 µm which covers the electromagnetic spectrum required for MIR molecular fingerprint region applications such as sensing and biological imaging.